Britain's Birds An Identification Guide to the Birds of Britain and Ireland - Hume, Rob 1950- (Princeton University Press, 2016)
Britain's Birds will be enjoyed and valued by everyone, from beginner to experienced birder. One of the most comprehensive, up-to-date and practical bird books of modern times, it features an unrivalled selection of photographs showing all the plumages you are likely to see. Focusing on identification, and containing maps, facts and figures on numbers and distributions, this breakthrough publication was devised by a team of lifelong birdwatchers, all with many years' experience of showing people birds and producing user-friendly field guides.Comprehensive coverage of every bird recorded in Britain and IrelandThe only photographic guide to show all plumages likely to be encounteredMore than 2,700 superb colour photographs carefully selected to show key identification featuresDetailed guidance to help you identify any bird you seeLatest information on status, population, distribution and conservation designations